The impact of a love language game intervention on relationship satisfaction among Chinese couples in China and Malaysia: examining the role of individualism-collectivism - Guanzheng Chen; Yanying Chen; Yuying Fan; Zhiying Zhang; Gaohuan Chen; Jin Wu; Nor Eeza Zainal Abidin (BMC Psychology)
Abstract Background Relationship satisfaction is crucial for the well-being and longevity of romantic relationships. Although love language interventions have demonstrated positive effects on relationship satisfaction, most research has focused on Western contexts. This study investigates the impact of a Love Language Game intervention on relationship satisfaction among Chinese couples in China and Malaysia and examines the role of individualism-collectivism in determining the intervention's effectiveness. Method Employing a mixed-methods approach and a randomized controlled trial design (RCT). The quantitative analysis utilized a two-way ANOVA to compare the Love Language Game intervention group with a control group participating in an alternative relationship enhancement workshop series. The qualitative component consisted of interviews exploring participants' experiences and perceptions of the interventions. Results The findings revealed the effectiveness of the Love Language Game intervention in improving relationship satisfaction among Chinese couples and highlighted the influence of individualism-collectivism on the intervention's outcomes. Participants' experiences and perceptions emphasized the significance of engagement, communication, cultural sensitivity, and tailored strategies in relationship interventions. Conclusion This study contributes to the literature on love language-based interventions and their application in culturally diverse settings, offering valuable insights for relationship counsellors, educators, and policymakers. The findings may guide the development and implementation of culturally sensitive interventions to enhance relationship satisfaction and overall well-being in diverse populations.